Penggunaan Art Therapy dan Dance Therapy untuk Meningkatkan Suasana Hati pada Penerima Manfaat Panti Pelayanan Sosial Disabilitas Mental Ngudi Rahayu Kendal - Siti Hikmah; Septiana Ambarwati; Sri Ayu Lestari; Anisa Arwah Lia (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to improve the atmosphere of the beneficiaries and help them express themselves through art therapy and dance therapy to reduce dependence on interventions through the media. The theory used in this research is art therapy as a medium for channeling expression and communicating thoughts and feelings through visual art. Apart from that, dance therapy combines physical movement and social interaction to relieve stress experienced by beneficiaries. The method used is a participatory method because it involves community members with a total of 15 beneficiaries (PM). Then for implementation it uses a pre-test and post-test by voting on sad and happy emoticons which must be chosen by the beneficiary. Apart from that, art therapy as a drawing medium, dance therapy as a physical movement activity, and interactive games as a group activity. The results of this study indicate that the two therapies used are effective in overcoming negative feelings and creating a positive mood